Crystal and molecular structure of fenspiride, C15H20N2O2. Issue 2 (June 2020) - Pagola, Silvina
Abstract : The crystal and molecular structure of fenspiride, a bronchodilator and anti-inflammatory drug, are reported. Fenspiride crystallizes in the monoclinic system, with two crystallographically independent molecules in the general position of the space group P 21 / n (No. 14) and Z = 8. Rietveld refined unit cell parameters are a = 11.52013(8) Å, b = 5.614091(31) Å, c = 44.1567(4) Å, α = 90°, β = 93.0885(6)°, γ = 90°, and V = 2851.69(4) Å 3 .